Progress and Challenges of the NRRP Low Carbon Economy Reforms in the Residential Building Sector in Bulgaria - TEODORA PENEVA (Global Economic Observer)
The article analyses the progress and challenges encountered in implementing low-carbon economy reforms within the building sector, as mandated by the National Resilience and Recovery Plan as a component of the instruments supporting the EU Green Deal. It highlights the role of the building sector in the broader policy framework for economic decarbonization, delves into the formulation of the reforms and identifies key issues within them, while also addressing the challenges faced in their execution. In conclusion, the article asserts that the anticipated outcomes of the reforms fall short of expectations, warranting a reassessment, redesign, or additional corrections for their effective application.